Workplace Violence in Mental Health: A Victorian Mental Health Workforce Survey. (24th June 2016) - Tonso, Michael A.; Prematunga, Roshani Kanchana; Norris, Stephen J.; Williams, Lloyd; Sands, Natisha; Elsom, Stephen J.
Abstract: The international literature suggests workplace violence in mental health settings is a significant issue, yet little is known about the frequency, nature, severity and health consequences of staff exposure to violence in Australian mental health services. To address this gap, we examined these aspects of workplace violence as reported by mental health services employees in Victoria, Australia. The project used a cross‐sectional, exploratory descriptive design. A random sample of 1600 Health and Community Services Union members were invited to complete a survey investigating exposure to violence in the workplace, and related psychological health outcomes. Participants comprised employees from multiple disciplines including nursing, social work, occupational therapy, psychology and administration staff. A total of 411 members responded to the survey (26% response rate). Of the total sample, 83% reported exposure to at least one form of violence in the previous 12 months. The most frequently reported form of violence was verbal abuse (80%) followed by physical violence (34%) and then bullying/mobbing (30%). Almost one in three victims of violence (33%) rated themselves as being in psychological distress, 54% of whom reported being in severe psychological distress. The more forms of violence to which victims were exposed, the greater the frequency of reports of psychological distress. Workplace violence is prevalent in mental health facilities in Victoria. The nature, severity and health impact of this violence represents a serious safety concern for mental health employees. Strategies must be considered and implemented by healthcare management and policy makers to reduce and prevent violence.